Kur’an bütünlüğü açısından surelerin baş tarafı ile sonu arasındaki münasebet - Tuncer, Faruk (My University, 2000)
There ıs no doubt that the Qur'an given by God. Every dimension of the Qur'an is a miracle. Because of this, this life's and the other life's happiness provider Qur'an, strike with admiration everyone. The deppness in words wide sense and rich concept of Qur'an caused this admiration. With this study we tried to expose one of the miracle in Qur'an. This study's aim is bring to light that in Qur'an relation between the beginings and the ends of the surahs are show no similarity with any other books. But we did this with taking care of the integrity in Qur'an. With the movement of commentary of Qur'an,it started to take up the relation between the beginning and the end of the surahs. But we can not say that these studies are satisfactory. So taking up this matter in doctorate level would be fill the blank in this area. So we tried to fill this blank area. We tried to reach every sources about this subject. However, modern studies take the central point in this doctorate. Particularly by taking care to. subjective commentary, which has taken a lot of way in last two century, it will be more easy to understand why we cansult to these sources freguently. Our study shaped in four part. In the first part, we take up relation theme. In the second part we tried to find out the place of our study's within the Qur'an sciences. In third and the fourth parth of this study, we point out the relation between the beginning and the end of the surahs, by means of integrity of Qur'an viewpoint. In the final part we summarized the outcomes of our study. A book which we have sent down to you, full of blessings, that they may ponder over its Verses, and that men of understanding may remember.
Keywords: İSLAM DİNİ-SURELER